Evaluation of Education Funding Policy: A Case Study of the Surabaya “Pemuda Tangguh” Scholarship Program - Tara Avrilyana Desvita; Meilisa Mufarocha; Andhika Abhinaya Ivanda; Indah Prabawati; Firre An Suprapto (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
Education is the most crucial aspect in measuring the progress of a nation. The Government of Indonesia guarantees the right to education and finances basic education for its citizens as part of its responsibility to educate the nation. However, the compulsory education program has not been fully realized, as evidenced by the existence of children who have not yet received formal education. One of the efforts made by the Surabaya City Government to improve access to education for underprivileged students in Surabaya is by launching the Pemuda Tangguh Scholarship Program. This study aims to evaluate the Pemuda Tangguh Scholarship Program in Surabaya. The research employs a qualitative approach using a case study method. Data collection techniques include observation and interviews with research subjects. The subjects consist of scholarship coordinators and student beneficiaries of the program. The study analyzes the program using policy evaluation theory proposed by William N. Dunn, which includes six indicators: effectiveness, efficiency, adequacy, equity, responsiveness, and appropriateness. The results show that the scholarship program has succeeded in expanding access to higher education, particularly for students enrolled in private universities in Surabaya. However, there are significant challenges related to the adequacy of financial assistance and responsiveness to public aspirations, especially concerning the reduction in the amount of aid, which has triggered complaints from beneficiaries.